Upaya Menciptakan Rasa Bangga Membeli Produk UMKM Naik Kelas Kabupaten Bogor - Dede Suleman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this activity is to provide knowledge of the importance of efforts to make the products produced, especially by MSMEs in Bogor Regency, acceptable to consumers. Because currently facing a condition where the products produced are still underestimated by consumers because most consumers currently consume products based on the manufacturer's brand and reputation, therefore this training was held to provide input to MSME actors. Bogor understands consumers in the new era. Where new things are needed to be done to arouse consumer buying interest in the products produced by this community. Several things are being done to make consumers buy by changing several production processes, including packaging which is the first impression seen by consumers to have curiosity and interest in buying the products they see on the market, regardless of this being an MSME product, but if it looks Interesting will make consumers become interested and decide to buy because they can feel a sense of pride for the products they buy judging from the first impression of the product.